ANALISIS KINERJA KEUANGAN PADA EXPEDISI LANCAR GROUP - Hani Krisnawati (Universitas Sains dan Teknologi Komputer, 2020)
This study aims to analyze the financial performance of the Salatiga Current Group Expedition, this study uses a descriptive qualitative approach. The research data are in the form of financial reports of the Current Expedition Group from 2014 to 2018. The research was conducted at the Current Expedition Group for 3 months which took place during August to October 2019. The purpose of this study was to look at the company's financial performance of the Current Expedition Group, reviewed in terms of liquidity, solvency and profitability by using descriptive research methods and data collection techniques in the form of documentation / literature in the form of secondary data, namely the annual report of the Current Expedition Group.